1995
DOI: 10.1111/j.1365-2141.1995.tb05592.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of RARa‐PML fusion mRNA detected by reverse transcriptase polymerase chain reaction in patients in long‐term remission of acute promyelocytic leukaemia

Abstract: Acute promyelocytic leukaemia (APL) is characterized by t(15;17), which results in the formation of two chimaeric genes, PML-RAR alpha and RAR alpha-PML. PML-RAR alpha transcripts have been detected in all cases of APL whilst those of RAR alpha-PML have been detected in only about 67% of cases. We have used reverse transcriptase polymerase chain reaction (RT-PCR) to detect both fusion transcripts serially in 18 patients in remission of APL after chemotherapy and bone marrow transplantation. All patients were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…24 However, 'end point' PCR analyses do not permit precise quantification of MRD levels. This limitation was underlined by the finding of low levels of AML1-ETO, 25,26 CBFB-MYH11 1 or PML-RARA 1,27 transcripts in patients in long-term clinical remission and by the detection of BCR-ABL mRNA at very low levels in healthy individuals. 28,29 Quantitative PCR analysis has been achieved by competitive PCR.…”
Section: Introductionmentioning
confidence: 99%
“…24 However, 'end point' PCR analyses do not permit precise quantification of MRD levels. This limitation was underlined by the finding of low levels of AML1-ETO, 25,26 CBFB-MYH11 1 or PML-RARA 1,27 transcripts in patients in long-term clinical remission and by the detection of BCR-ABL mRNA at very low levels in healthy individuals. 28,29 Quantitative PCR analysis has been achieved by competitive PCR.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in keeping with our previous work which showed that some APL patients in long-term remission are positive for the reciprocal fusion gene RARA-PML transcripts. 6 Although a number of groups have worked on improving the sensitivity of PML-RARA amplification, 19,20 this study is the first to show that improving method sensitivity could detect the persistence of PML-RARA transcripts in patients in longterm remission.…”
Section: Discussionmentioning
confidence: 99%
“…1 This translocation fuses the PML gene on 15q and RARA gene on 17q to produce two transcriptionally active fusion genes PML-RARA and RARA-PML. [2][3][4][5][6] Transcripts for PML-RARA were detected in all patients with t(15;17) while RARA-PML transcripts were detected in approximately 70% of cases. 4 RT-PCR methods developed for the amplification of PML-RARA transcripts have been used for diagnosis and in monitoring minimal residual disease (MRD).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…[41][42][43] However, this correlation is not absolute as some patients who are PCR positive remain in long-term remission, and others ultimately relapse after a negative test. [44][45][46] Although assessment of the PCR status immediately following the end of consolidation has little prognostic value, subsequent monitoring during the early post-treatment period appears informative and affects management of this disease. Recently, Diverio and colleagues 42 reported the results of a prospective study in which 163 patients who were induced into remission with ATRA combined with chemotherapy were tested at regular pre-established time intervals after the end of treatment.…”
Section: The Issue Of Molecular Relapsementioning
confidence: 99%